Adolescents’ Motivational Profiles in Mathematics and Science: Associations With Achievement Striving, Career Aspirations and Psychological Wellbeing - Watt, Helen M. G.; Bucich, Micaela; Dacosta, Liam (Frontiers in Psychology, 2019)
Pertinent to concern in Australia and elsewhere regarding shortages in STEM fields, motivational expectancies and values predict related study and career aspirations. Less is known about how “cost” values may deter, and how expectancies/values and costs combine for different profiles of learners to predict achievement aspirations and wellbeing outcomes. These were the present study aims using established measures of perceived talent, intrinsic and utility values, and a new multidimensional “costs” measure as the platform to explore a typology of mathematics/science learners, gender and achievement influences, achievement striving, related career aspirations and personal wellbeing. Grade 10 Australian adolescents (N = 1,172; 702 girls) completed surveys early 2012/2013, from 9 metropolitan Sydney/Melbourne schools. Grade 9 background achievement data in mathematics were nationally assessed numeracy scores, and in science were self-reported usual results. Experienced learning environments were perceived mastery/performance. Achievement-striving measures were aimed marks and efforts exerted. Mathematics/science-related career aspirations were subjectively rated by students, and objectively rated from open-ended stated career plans. Depression, anxiety and stress scales tapped personal wellbeing. Latent profile analyses educed profiles within each of mathematics and science domains: “Positively engaged” scored high on positive motivations, low on costs; “Struggling ambitious” were high for both positive motivations and costs; “Disengaged” exhibited generally low scores on positive motivations but high costs. MANOVAs examined mathematics/science profile differences on clustering variables, experienced learning environments, achievement background and striving, career aspirations and wellbeing. Chi-square tested associations with gender, and profile differences across mathematics and science. Similar profiles for mathematics and science, and coherent pattern of antecedents and outcomes, prompt several theoretical and educational implications.